Intelligent design of nondefective welding technology - Kaminskas, Tomas; Kulvietis, Genadijus; Keblas, Leonas (Lietuvos matematikos rinkinys, 2001)
In the process of welding the objective and subjective factors are existing and the defects of welded joints may occur under their influence. The higher level of welded joints can be reached while using the weld joint design on the computer based programme. The expert system and it structure of non-defect design of welded joints has been reviewed in the work. The programme helps to select the optimal welding parameters and allows decreasing of objective and subjective defects to occur as well as correcting welding parameters if any defect occurs.